Centrifuge modelling of active slide–pipeline loading in soft clay - Boylan, Noel; Fauzan, Sahdi; Gaudin, Christophe; White, David J. (Plum Analytics, 2014)
Submarine slides are a significant hazard to the safe operation of pipelines in the proximity of continental slopes. This paper describes the results of a centrifuge testing programme aimed at studying the impact forces exerted by a submarine slide on an offshore pipeline. This was achieved by dragging a model pipe at varying velocities through fine-grained soil at various degrees of consolidation, hence exhibiting properties spanning from the fluid to the geotechnical domains, relevant to the state of submarine slide material. To simulate the high strain rates experienced by the soil while flowing around a pipe in the path of a submarine slide, tests were conducted at pipe–soil velocities of up to 4.2 m/s. The changing density and shear strength of the samples were back-calculated from T-bar penetrometer test results. A hybrid approach combining geotechnical and fluid-mechanics-based components of horizontal drag resistance was developed. This approach provides an improved method to link the density and strength of the slide material to the force applied on the pipe. Besides fitting the present observations, the method provides an improved reinterpretation of similar data from the literature.